Finding Science and Engineering Specific Data Set Usage or Funding Acknowledgements. - Ann Coppin (Issues in Science and Technology Librarianship, 2013)
The article tackles a study which reviewed the pertinent publications about studying acknowledgements and described how to find funding or source data information. Examples of actual search for acknowledgement metrics are presented, including the use of U.S. National Aeronautics and Space Administration Time on the Keck Telescope, use of the Gravity Recovery and Climate Experiment Tellus Web site by scientists, and papers by authors who are supported by the Cassini Data Analysis Program.